2014
DOI: 10.14411/eje.2014.026
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Prunus serotina - a new host for Yponomeuta evonymellus (Lepidoptera: Yponomeutidae)?

Abstract: Abstract. Introduction of non-native species of plants affects the existence and feeding preferences of herbivorous insects. The bird cherry ermine moth (Yponomeuta evonymellus) is considered a typical monophagous insect, which feeds only on bird cherry (Prunus padus) leaves. However, in recent years, we have observed Y. evonymellus larvae feeding on leaves of the non-native (in Europe) and highly invasive black cherry (Prunus serotina). We hypothesized that this insect can feed on P. serotina leaves with no n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…For example, invasive Prunus serotina Ehrh. demonstrates a strong and close phylogenetic relationship with native P. padus L. (Bortiri et al 2001), and differences in food quality are small, so native specialists (Karolewski et al 2014) and generalists (Nowakowska and Halarewicz 2006;Mąderek et al 2015) have adapted to carrying out the entire life cycle with this new plant. Between Salix viminalis and Spiraea tomentosa, there is no close phylogenetic affinity, and our measurements show that the leaves of these two species differ significantly in relation to both chemical and morphological features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, invasive Prunus serotina Ehrh. demonstrates a strong and close phylogenetic relationship with native P. padus L. (Bortiri et al 2001), and differences in food quality are small, so native specialists (Karolewski et al 2014) and generalists (Nowakowska and Halarewicz 2006;Mąderek et al 2015) have adapted to carrying out the entire life cycle with this new plant. Between Salix viminalis and Spiraea tomentosa, there is no close phylogenetic affinity, and our measurements show that the leaves of these two species differ significantly in relation to both chemical and morphological features.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in the number of natural enemies is usually observed in the case of plant species relocated beyond their natural range (Keane and Crawley 2002), but native insect species are able to utilise neophyte plant species (e.g. Karolewski et al 2014). Based on the literature, the impact of alien plants on insects and their host selection preferences remains equivocal (Sunny et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have clearly showed the adverse effects of black cherry invasions in forest stands including limiting recruitment of native species (Vanhellemont et al 2010), shifting forest community structure (Halarewicz and Żołnierz 2014) or even changing ecosystem functioning by altering nutrient cycling leading to a reduced carbon sequestration capacity of native species (Aerts et al 2017). Leaves of P. serotina are successfully used as an alternative food source for native insect pests (Karolewski et al 2014) that increases the food base for the insect pests of the native bird cherry (Prunus padus L.). Currently, there is no efficient method for invader eradication.…”
Section: Introductionmentioning
confidence: 99%
“…Herbivorous insects have been observed on P. serotina (Halarewicz and Jackowski, 2011;Karolewski et al, 2014;Halarewicz, 2006a, 2006b); a range of insect, bird, and mammal species feeds on P. serotina fruits (Boucault, 2009;Deckers et al, 2008;Korringa, 1947); and P. serotina seeds are predated by rodents (Boucault, 2009;Eijsackers and Ham, 1990) and the bird-cherry weevil (Moraal, 1988;Pairon et al, 2006). Pre-dispersal seed predation, as by the bird-cherry weevil Furcipus rectirostris (Linnaeus 1758), has not yet been reported in P. serotina's native range (e.g., Marquis, 1990).…”
Section: Introductionmentioning
confidence: 99%